Management of complex surgical wounds of the back: identifying an evidence-based approach - Elizabeth G. Zolper; Meher A. Saleem; Kevin G. Kim; Mark D. Mishu; Sarah R. Sher; Christopher E. Attinger; Kenneth L. Fan; Karen K. Evans (Archives of Plastic Surgery, 2021)
Background Postoperative dehiscence and surgical site infection after spinal surgery can carry serious morbidity. Multidisciplinary involvement of plastic surgery is essential to minimizing morbidity and achieving definitive closure. However, a standardized approach is lacking. The aim of this study was to identify effective reconstructive interventions for the basis of an evidence-based management protocol. Methods A retrospective review was performed at a single tertiary institution for 45 patients who required 53 reconstruction procedures with plastic surgery for wounds secondary to spinal surgery from 2010 to 2019. Statistical analysis was performed for demographics, comorbidities, and treatment methods. Primary outcomes were postoperative complications, including dehiscence, seroma, and infection. The secondary outcome was time to healing. Results The overall complication rate was 32%, with dehiscence occurring in 17%, seroma in 15% and infection in 11% of cases. Median follow-up was 10 months (interquartile range, 4–23). Use of antibiotic beads did not affect rate of infection occurrence after wound closure (P=0.146). Use of incisional negative pressure wound therapy (iNPWT) was significant for reduced time to healing (P=0.001). Patients treated without iNPWT healed at median of 67.5 days while the patients who received iNPWT healed in 33 days. Demographics and comorbidities between these two groups were similar. Conclusions This data provides groundwork for an evidence-based approach to soft tissue reconstruction and management of dehiscence after spinal surgery. Timely involvement of plastic surgery in high-risk patients and utilization of evidence-based interventions such as iNPWT are essential for improving outcomes in this population.